The Effect of Risk Management Implementation on Toll Road Transportation Performance: Literatur Review - Panjaitan, Juhri; Harahap, Muhammad Wandi; Andrika, Nuansah; Hasibuan, Abdurrozzaq (AMK : Abdi Masyarakat UIKA, 2025)
OHS risk management is a structured process that aims to identify, analyze, and manage risks associated with occupational health and safety. In the context of highway projects, such risks may include occupational accidents, contact with hazardous materials, and unsafe work situations, By implementing effective OHS risk management, companies can reduce the likelihood of accidents, increase worker safety, and ultimately improve overall project performance. This research uses library research or literature study. To find data for literacy studies, you can refer to books, research journals published locally and internationally, scientific writings, research conducted by others. A literature review is a summary of the literature on a topic. Based on the analysis of various journals on the implementation of occupational safety and health (OHS) risk management in toll road projects, it can be concluded that OHS risk management has an important role in improving the safety and performance of construction projects. Although many studies show good results, such as improved alignment of risk management systems and efficient implementation of preventive measures, challenges in implementation still remain.